Effects of Place-Based Socioscientific Issues on Rising Middle School Students’ Evidence-Based Reasoning and Critical Thinking on Hydraulic Fracking - Wardell A. Powell (Journal of Education in Science, Environment and Health)
This study investigated the implementation of a place-based socioscientific issue curricular unit designed to improve rising middle school students’ abilities to think critically about the pros and cons of hydraulic fracturing and engage in evidence-based reasoning on whether the practice should be banned in Massachusetts. Forty-three rising middle school students from a summer enrichment program for science, mathematics, reading and writing operated by a non-profit organization in the northeastern United States participated in this study. The instructional unit exposed the students to information and activities on hydraulic fracturing for five consecutive days (50 minutes each day). The findings from this study showed that through productive socioscientific issues pedagogy, the students used the evidence collected from their investigation to engage in evidence-based reasoning about the cost and benefits of hydraulic fracturing on the public health, economy, and the environment. The students used their understanding of the science and engineering practices to construct valid arguments on whether or not hydraulic fracturing should be allowed in their state. The results further indicate that the use of socioscientific issues as a critical pedagogical strategy can equip students with the skills necessary for them to become better advocates for themselves and their communities.